Il primo Concilio di Costantinopoli (381). Uno schizzo storico e teologico - Degórski, Bazyli (Vox Patrum, 2016)
Article briefly discusses the history, or rather “pre-history”, of the First Ecumenical Council of Constantinople (381), highlighting all those people who have made an outstanding contribution to his calling and have an impact on the course of its deliberations, as well as to develop and solemn announcement dogma concerning the deity of the Holy Spirit. Thus, the article focuses on the diplomatic and theological activities of Cappadocian Fathers as such, but primarily focuses on the person of the bishop of Caesarea in Cappadocia – St. Basil the Great.